1
$\begingroup$

In the opening lines of Spivaks "Calculus on Manifolds" proof of the inverse function theorem he writes the equation below. let $\lambda = Df(a)$ $$D(\lambda^{-1}\circ f)(a) = D(\lambda^{-1})(f(a))\circ Df(a) = \lambda^{-1}\circ Df(a)$$

I don't see how $ D(\lambda^{-1})(f(a)) = \lambda^{-1}$ in the second equality

and in the statment of the theorem makes the standard assumptions of f being $c^1$ and $f'(a)$ being nonsingular.

$\endgroup$

1 Answer 1

2
$\begingroup$

It's simply because $\lambda$ is a linear map. So, its inverse is also a linear map and the derivative of a linear map at every point of its domain is again that linear map.

$\endgroup$
1
  • $\begingroup$ I forgot that property. thanks! $\endgroup$ Jun 4, 2018 at 14:41

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .